Disputing cultural policies for the Argentine circus in times of pandemic and post-pandemic - Infantino, Julieta (Revista de Antropología Social, 2026)
This article analyzes a contested terrain within the realm of cultural policies that transcends the exclusively state sphere, focusing on the processes of politicization driven by historically marginalized and/or subalternized sectors. Through their demands, these groups influence the configuration of public policy, with variable outcomes in terms of effectiveness. The study centers on the organization of circus artists and their demands for recognition and specific policies for the sector. It examines the period between 2019 and 2023, during which the circus entered for the first time on the official agenda of national cultural policy. The research studies the evolution of relations between the artists and the state during the pandemic and post-pandemic period, highlighting both achievements and the complexities, frictions, advancements, and setbacks. The data utilized derive from various sources, including conventional methods of anthropological research such as interviews and participant observation, as well as collaborative approaches that were deployed through my active involvement in the field.
Keywords: circus; cultural policy; political organization; pandemic/post-pandemic